The Peculiarities of the X-XII Form Student's Tolerance Understanding - Sprindžiūnas, Andrius (Acta Paedagogica Vilnensia, 2000)
Tolerance education is an important issue for most contemporary societies. This article presents results of the X-XII form students’ tolerance attitude research in Vilnius secondary schools. It reveals some peculiarities of students' understanding the tolerance and other related values. Also it reveals some significant differences in age, sex facets, etc. Analysis of statistical data reveals that only half of the students are competent to apprehend the concept of the tolerance property. This research material could help to look for new ways to found a more tolerant and more human society.
Keywords: Tolerance; tolerance education; concept of tolerance; senior pupils; secondary school.